Autoimmune encephalitis: novel therapeutic targets at the preclinical level. (2nd January 2021) - Sell, Josefine; Haselmann, Holger; Hallermann, Stefan; Hust, Michael; Geis, Christian
ABSTRACT: Introduction: Antibody-mediated encephalitides (AE) with pathogenic autoantibodies (aAB) against neuronal surface antigens are a growing group of diseases characterized by antineuronal autoimmunity in the brain. AE patients typically present with rapidly progressive encephalitis and characteristic disease symptoms dependent on the target antigen. Current treatment consists of an escalating immunotherapy strategy including plasma exchange, steroid application, and B cell depletion. Areas covered: For this review, we searched Medline database and google scholar with inclusive dates from 2000. We summarize current treatment strategies and present novel therapeutic approaches of target-specific interventions at the pre-clinical level as well as immunotherapy directed at antibody-induced pathology. Treatment options include modulation of target proteins, intervention with downstream pathways, antibody modification, and depletion of antibody-secreting cells. Expert opinion: Although current therapies in AE are effective in many patients, recovery is often prolonged and relapses as well as persistent deficits can occur. Specific immunotherapy together with supportive target-specific therapy may provide faster control of severe symptoms, shorten the disease course, and lead to long-lasting disease stability. Among the various novel therapeutic approaches, modulation of targeted receptors by small molecules crossing the blood-brain barrier as well as prevention of aAB binding is of particular interest.